2022
DOI: 10.1101/2022.07.04.22277120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Physical Exercises on Emotion Regulation: A Meta-Analysis

Abstract: BackgroundAt present, there are inconsistent results in the research on the effect of physical exercise on emotion regulation ability, and there is no relevant research on how to exercise scientificlc. Therefore, on the basis of previous research, this study conducted a meta-analysis on the theme of physical exercise affecting emotion regulation ability according to the statement of PRISMA, and added relevant moderator variables to clarify the effect of physical exercise on emotion regulation ability.Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Research in adults and older children suggests that physical ac2vity provides both immediate and long-term benefits for emo2on regula2on and execu2ve func2on (Best, 2010;Liu et al, 2022). These findings suggest physical ac2vity may offer an effec2ve in-themoment tool to address emo2on dysregula2on in early childhood and enhance overall regula2on skills with prolonged use.…”
Section: Immediate and Long-term Effects Of Physical Ac/vitymentioning
confidence: 91%
See 2 more Smart Citations
“…Research in adults and older children suggests that physical ac2vity provides both immediate and long-term benefits for emo2on regula2on and execu2ve func2on (Best, 2010;Liu et al, 2022). These findings suggest physical ac2vity may offer an effec2ve in-themoment tool to address emo2on dysregula2on in early childhood and enhance overall regula2on skills with prolonged use.…”
Section: Immediate and Long-term Effects Of Physical Ac/vitymentioning
confidence: 91%
“…While this area of research is in its infancy in early childhood, evidence from research conducted with older children and adults is more abundant and provides moderate evidence that engaging in physical ac2vity offers benefits for emo2on regula2on, and more specifically, provides therapeu2c effects on the autonomic nervous system (Basso & Suzuki, 2017;Berger & Motl, 2000;Davidson et al, 2007;Liu et al, 2022). Evidence from a recent meta-analysis of 11 randomised control trials conducted with adolescents and adults reported that both long-term and acute bouts of physical ac2vity offer benefits for emo2on regula2on; reducing the dura2on of nega2ve affect and levels of sensory arousal in response to a stressor, and increasing the use of emo2on regula2on strategies (Liu et al, 2022).…”
Section: Effects Of Physical Ac/vity On Emo/on Regula/onmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies associate the beneficiary effects of PEs with the upregulation of BDNF, an essential component of neuroplasticity ( Kim et al, 2020 ; Müller et al, 2020 ; Nicolini et al, 2020 ; Park et al, 2020 ; Sugiyama et al, 2020 ), and with the transient increase in the availability of BDNF in the brain ( Knaepen et al, 2010 ; Quan et al, 2020 ; Walsh et al, 2020 ). Since the mechanisms of PEs’ profitable effects may be similar to that of antidepressants ( Björkholm and Monteggia, 2016 ; Castrén and Kojima, 2017 ), it is not surprising that PEs are beneficial in the improvement of regulation of emotional status ( Zhang et al, 2019a ; Liu et al, 2022 ). In addition to altering synapse wiring, PEs can induce neuroplasticity by acting on auxiliary functions that can lead to neuroplasticity, such as glial activation and angiogenesis ( Morland et al, 2017 ; Li et al, 2021 ).…”
Section: Physical Exercises As An Alternative To the "Easy Come-easy ...mentioning
confidence: 99%
“…Social-emotional competency mainly includes social competency and emotional competency (Choi and Gwag, 2017). Studies have shown that physical exercise has a positive effect on social competency and emotional control skills (Jiang et al, 2018;Liu J. et al, 2022). Lack of socialemotional competency is the root cause of various psychological and behavioral problems, which seriously hinder students' academic progress and the growth of body and mind (Rautakoski et al, 2021).…”
Section: Mediating Effect Of Social-emotional Competencymentioning
confidence: 99%